A Islamic financing and Implementation of Sustainability Development Goals: Prospect & challanges - Hedy Maulana, Bonnix; Eka Harjanti, Agustina; Dena Ameliani, Rosy (International Economic Conference of Business and Accounting, 2024)
This study thoroughly examines the potential and challenges of Islamic financing in driving the achievement of the Sustainable Development Goals (SDGs). Through an extensive literature review, the research meticulously analyzes the impact of Islamic financial instruments, particularly those that adhere to Sharia principles, on sustainable development. The study unequivocally demonstrates that Islamic financing, particularly through instruments such as green sukuk, presents substantial opportunities for funding environmentally friendly projects, thus playing a pivotal role in transitioning towards a green economy. Notwithstanding, the broader adoption of Islamic financing faces challenges including regulatory inconsistencies, low financial literacy, and the imperative need for greater harmonization of Sharia standards across different countries. The research emphatically underscores the significance of robust regulatory frameworks and comprehensive public awareness campaigns to optimize the transformative potential of Islamic financing in advancing the SDGs. Furthermore, it strongly advocates for future research to prioritize empirical studies aimed at assessing the concrete impact of specific Islamic financial products on sustainable development outcomes. The study concludes with assertive recommendations for policymakers, stressing the urgency for regulatory harmonization and intensified educational efforts to promote the understanding and utilization of Islamic financing.